The management of adult female patients with Eisenmenger syndrome and advanced pulmonary arterial hypertension treatment: single center experience and follow-up for 5 years - Gülten Taçoy; Hatice Duygu Başer; Sedat Türkoğlu; Atiye Çengel (KARE Publishing, 2014)
Objectives: Eisenmenger syndrome (ES) occurs as the most advanced form of pulmonary arterial hypertension (PAH) in patients with congenital heart disease. In this study, we aimed to evaluate the management of ES patients, follow-up and specific PAH treatment applying and clinical outcomes during 5 years. Study design: During the period of the month between May 2008 and 2013 ES female patients were included in the study and followed an average for 5 years. Clinical findings, brain natriuretic peptide levels, transthoracic and right heart catheterization findings, 6-min walking test distance were recorded. PAH specific treatment as bosentan, iloprost and sildenafil was given to patients according to guidelines. The patients were evaluated with 3 months intervals as requirement for hospitalization, combination treatment, and mortality. Results: A total of 12 patients were included in the study. All of the patients were women, the mean age was 36.5. As prognostic echocardiographic data, the patients had high pulmonary artery pressure (109.81+-24.94 mmHg) related with increased right ventricular wall thickness, elevated right atrial pressure, severe pulmonary regurgitation in 40%, shortened pulmonary acceleration time, diminished myocardial tissue Doppler velocities of the left and right ventricles, increased right atrium area/ left atrial area ratio (1.35+-0.40), lower right ventricular fractional area change. During the follow-up period of 5 years, a total of 16 events occurred. Combination treatment was required in 8 patients. Conclusion: Eisenmenger syndrome is a multi-system affecting disease and due to high morbidity and mortality risk patients with ES should be followed by specialized centers. PAH specific treatment improves the disease course and survival of patients.